A review on traditional uses, phytochemistry, pharmacology, pharmacokinetics and toxicology of the genus Peganum. (5th May 2017) - Li, Shuping; Cheng, Xuemei; Wang, Changhong
Abstract: Ethnopharmacological relevance: The plants of the genus Peganum have a long history as a Chinese traditional medicine for the treatment of cough, hypertension, diabetes, asthma, jaundice, colic, lumbago, and many other human ailments. Additionally, the plants can be used as an amulet against evil-eye, dye and so on, which have become increasingly popular in Asia, Iran, Northwest India, and North Africa. Aim of the review: The present paper reviewed the ethnopharmacology, phytochemistry, analytical methods, biological activities, metabolism, pharmacokinetics, toxicology, and drug interaction of the genus Peganum in order to assess the ethnopharmacological use and to explore therapeutic potentials and future opportunities for research. Materials and methods: Information on studies of the genus Peganum was gathered via the Internet (using Google Scholar, Baidu Scholar, Elsevier, ACS, Pudmed, Web of Science, CNKI and EMBASE) and libraries. Additionally, information was also obtained from some local books, PhD and MS's dissertations. Results: The genus Peganum has played an important role in traditional Chinese medicine. The main bioactive metabolites of the genus include alkaloids, flavonoids, volatile oils, etc. Scientific studies on extracts and formulations revealed a wide range of pharmacological activities, such as cholinesterase and monoamine oxidase inhibitory activities, antitumor, anti-hypertension, anticoagulant, antidiabetic, antimicrobial, insecticidal, antiparasidal, anti-leishmaniasis, antioxidant, and anti-inflammatory. Conclusions: Based on this review, there is some evidence for extracts' pharmacological effects on Alzheimer's and Parkinson's diseases, cancer, diabetes, hypertension. Some indications from ethnomedicine have been confirmed by pharmacological effects, such as the cholinesterase, monoamine oxidase and DNA topoisomerase inhibitory activities, hypoglycemic and vasodilation effects of this genus. The available literature showed that most of the activities of the genus Peganum can be attributed to the active alkaloids. Data regarding many aspects of the genus such as mechanisms of actions, metabolism, pharmacokinetics, toxicology, potential drug interactions with standard-of-care medications is still limited which call for additional studies particularly in humans. Further assessments and clinical trials should be performed before it can be integrated into medicinal practices. Graphical abstract: